The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/pd.2484
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology to preserve the original proportion and integrity of cell‐free fetal DNA in maternal plasma during sample processing and storage

Abstract: Using Streck's Cell-free DNA BCT tubes, it is possible to preserve the original proportion of fetal cell-free DNA for extended times as well as minimize the post-sampling maternal cell-free DNA background. Preserved in this way, fetal cell-free DNA can be amplified by WGA technology to be used in prenatal diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 24 publications
(35 reference statements)
3
68
2
1
Order By: Relevance
“…The use high centrifugal force may destroy blood cells and release maternal DNA, subjecting it to the effects of DNases (Fernando et al, 2010). Thus, a two-step centrifugation process was used.…”
Section: Discussionmentioning
confidence: 99%
“…The use high centrifugal force may destroy blood cells and release maternal DNA, subjecting it to the effects of DNases (Fernando et al, 2010). Thus, a two-step centrifugation process was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fernando et al [34] demonstrated that cfDNA levels in blood samples drawn in cell-free DNA TM blood collection tubes were stable for up to 14 days at RT, while they decreased when blood was drawn in K3EDTA collection tubes. Barrett et al [28] showed that there was no significant difference for up to 3 days in the total cfDNA concentration when blood was drawn in cell-free DNA TM blood collection tubes, while it increased after 24 h when blood was drawn in K3EDTA collection tubes.…”
Section: Blood Collection Tubesmentioning
confidence: 95%
“…Recently cell-free DNA blood collection tubes (BCT) were introduced containing a stabilizing substance that prevents the extracellular DNA from being diluted by cellular DNA [267]. The use of these tubes might be a good choice when samples have to be shipped for processing to another laboratory but when the blood samples are processed in a reasonable time (several hours to 1 day) EDTA collection tubes are not inferior [268].…”
Section: Pre-analytic Variablesmentioning
confidence: 99%